A gradient sensing middleware to handle flash flood. (August 2017) - Ahmed, Nova; Ghosh, Shuvashis; Hassan, Rifat Ahmed; Galib, Sian Iftekher; Azad, A.K.; Syrus, Minhaz Ahmed
Abstract: Flash Flood is a natural disaster that floods away large area in a sudden manner. Bangladesh is affected by this natural disaster and loses valuable assets regularly. We currently have developed a system that has cloud infrastructure for intelligent long term data processing and low cost sensing devices that are able to make local decisions in its surrounding area. The system is adopted to work in a developing country such as low cost sensing that is locally available along with ability to adapt to sparse network infrastructure. Our system is called Shonabondhu: Golden Friend in Bengali, and we share our design, development and evaluation cycle of this system.